Analisis Strategi Transformasi Digital dalam Meningkatkan Keunggulan Bersaing Organisasi - Ipuk Widayanti; Avysach Aldi Tanduklangi (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
Digital transformation has become a strategic issue that is inseparable from the dynamics of organizational competition in the digital economy era. Changes in the business environment driven by the rapid development of information technology, market disruption, and increasing customer expectations require organizations to continuously adapt their business strategies. This study aims to analyze the role of digital transformation strategies in enhancing organizational competitive advantage and to identify the strategic challenges faced during their implementation. The research adopts a descriptive qualitative approach through a literature review by examining national and international scientific journals, reports from global institutions, and relevant official publications related to strategic management and digital transformation. The findings indicate that digital transformation significantly contributes to improving operational efficiency, fostering business model innovation, and strengthening organizational value creation. However, the success of digital transformation is highly influenced by human resource readiness, strategic leadership, and alignment between technology adoption and organizational objectives. This study provides managerial implications for organizations in formulating sustainable digital transformation strategies to achieve long-term competitive advantage.